539 Post-Covid-19 Smell Clinic - Management of Patients With 'Long Covid'. (12th October 2021) - Gopikrishna, D; Rocke, J; Chu, M; Kumar, N
Abstract: Introduction: Olfactory dysfunction following COVID-19 infection is a prevalent issue in the post-viral phase of illness. Around 50% of patient's self-report loss of sense of smell with COVID-19. Approximately 10% of these patients report no recovery in sense of smell at 4-6 weeks after onset. Patients with olfactory dysfunction often describe life as living in 2D, with lasting effects on eating habits and relationships. The aim of this project was to establish a novel 'Post-Covid-19 smell clinic' for patients, which monitored any changes relating to olfactory dysfunction and to provide advice on management of the condition for these patients with "Long-Covid". Method: The 'smell clinic' was set up based on BRS guidelines. Patients were asked to carry out the 'UPSIT' smell test and eODQ questionnaire. Patients were then advised to carry out 'smell retraining' for 4 months and pointed to appropriate resources. We analysed patients' presentations to identify patterns that may identify patients who are likely to suffer long term olfactory dysfunction following Covid-19 infection. Parameters including prevalence of parosmia, cacosmia, dysgeusia, demographics were collected. Results: Initial data, from 20 patients, showed 40% experienced parosmia and 40% had associated rhinological symptoms such as rhinorrhoea. The range UPSIT score: 22-34, eODQ score: 42-151. Conclusions: Our initial analysis of the clinic identified symptoms range from anosmia, parosmia and loss of flavour. Parosmia patients experienced this in relation to smells such as excrement and coffee. Future implications involve analysing the possible benefits of 'smell retraining' after repeating UPSIT and the eODQ score